To use a simple hernia needle for single-port laparoscopic percutaneous inguinal hernia repair in children: a 5-year experience study - Zhang, Li; Zhang, Rui; Zhang, Jianfa; Hu, Hailong; Chen, Zihan; Fu, Yanxiang; Li, Saihua (Frontiers in Pediatrics, 2024)
Purpose The aim of this study is to investigate the technique and practical significance of using a simple hernia needle in single-port laparoscopic herniorrhaphy in pediatric patients. Methods The study conducted a retrospective analysis of all pediatric patients who underwent treatment for inguinal hernia using single-port laparoscopic herniorrhaphy with a simple hernia needle at Yellow River Sanmenxia Hospital from June 2018 to May 2023. The medical records of all the children were collected, and clinical characteristics, procedural information, and follow-up data were carefully reviewed. Results A total of 848 patients underwent inguinal hernia repair, with ages ranging from 7 months to 13 years (2.99±2.49 years), including 756 males and 92 females. A total of 528 cases of unilateral hernia and 310 cases of bilateral hernia were reported, with intra-operative findings revealing contralateral occult hernia in 253 cases. Single-port laparoscopic herniorrhaphy was successfully completed in all patients, with no instances of conversion to open surgery. The mean operation time for unilateral hernia repair was (7.50±4.80) minutes, while for bilateral hernia repair it was (11.55±7.27) minutes. Five patients presented with subcutaneous emphysema, while two patients experienced a recurrence of inguinal hernia. No complications, such as scrotal hematoma, trocar umbilical hernia and testicular atrophy, were observed. The duration of the follow-up period ranged from 3 to 24 months. Conclusion The promotion and utilization of single-port laparoscopy combined with a simple hernia needle in clinical practice are justified. Our initial investigation indicates that this surgical approach is both safe and dependable for the management of pediatric inguinal hernia. The procedure presents numerous benefits, including the utilization of uncomplicated instruments, straightforward operation, a clear curative impact, minimal tissue damage, rapid recovery, and the absence of scarring.